2001
DOI: 10.1177/104973150101100602
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Men’s Batterer Treatment Groups

Abstract: Objective: Fifteen treatment groups for men who abused intimate partners were evaluated. Method: 104 men took part, with a completion rate of 68.3%. Scores on social desirability were utilized to adjust totals on other self-report scales. Results: Group completers (n = 71) were no different from dropouts (n = 33) on the adjusted standardized measures or demographics. Group completion was associated with significant improvements on the adjusted variables of appraisal social support, self-esteem, perceived stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 54 publications
2
23
0
1
Order By: Relevance
“…For instance, Dutton et al (1997b) found that voluntary treatment participants had a signifi cantly longer time until fi rst assault. However, beyond a higher level of perceived stress for court-mandated offenders at post-treatment, Tutty et al (2001) found no differences between court-mandated and voluntary treatment participants.…”
Section: Factors Related To Domestic Violence Perpetration Treatmentmentioning
confidence: 95%
See 4 more Smart Citations
“…For instance, Dutton et al (1997b) found that voluntary treatment participants had a signifi cantly longer time until fi rst assault. However, beyond a higher level of perceived stress for court-mandated offenders at post-treatment, Tutty et al (2001) found no differences between court-mandated and voluntary treatment participants.…”
Section: Factors Related To Domestic Violence Perpetration Treatmentmentioning
confidence: 95%
“…Despite lingering disagreement about the effectiveness of domestic violence treatment, it appears that domestic violence treatment results in some positive changes in batterers who complete it (Babcock et al, 2004, Davis and Taylor, 1999, Dutton et al, 1997a, Hamberger and Hastings, 1988and Tutty et al, 2001. Moreover, batterers who complete domestic violence treatment are less likely to subsequently recidivate and have fewer re-assaults when they do recidivate than those who drop out of treatment (Chen et al, 1989and Dutton et al, 1997bHamberger and Hastings;.…”
Section: Directions and Considerations For Future Researchmentioning
confidence: 99%
See 3 more Smart Citations